Time-dependent diffusion in pulsating white dwarf stars: Asteroseismology of G117-B15A - Benvenuto, Omar Gustavo (2002)
We study the structural characteristic of the variable DA white dwarf G117-B15A by applying the methods of asteroseismology. For such a purpose, we construct white dwarf evolutionary models considering a detailed and up-to-date physical description as well as several processes responsible for the occurrence of element diffusion. We have considered several thicknesses for the outermost hydrogen layer, whereas for the inner helium-, carbon- and oxygen-rich layers we considered realistic profiles predicted by calculations of the white dwarf progenitor evolution. The stellar masses we have analysed cover the mass range of 0.50 ≤ M⁎/M⊙ ≤ 0.60. The evolution of each of the considered model sequences was followed down to very low effective temperatures; in particular, from 12 500 K on we computed the dipolar, linear, adiabatic oscillations with radial order k = 1,..., 4. We find that asteroseismological results are not univocal regarding mode identification for the case of G117-B15A. However, our asteroseismological results are compatible with spectroscopic data only if the observed periods of 215.2, 271.0 and 304.4 s are due to dipolar modes with k = 2, 3, 4, respectively. Our calculations indicate that the best fit to the observed period pattern of G117-B15A corresponds to a DA white dwarf structure with a stellar mass of 0.525 M⊙, with a hydrogen mass fraction log(MH/M⁎) ≳ -3.83 at an effective temperature Teff ≈ 11 800 K. The value of the stellar mass is consistent with that obtained spectroscopically by Koester & Allard.